Sustainable Development of Human Resources of the EEU Countries in the Integrated Labor Market - DOSKALIYEVA, Bayan; KARENOVA, Gylnar; RAKHIMOVA, Gulmira; TLEUZHANOVA, Manatzhan; KASENOVA, Asiya; POPOVA, Lyubov (Journal of Advanced Research in Law and Economics; Vol 8 No 6 (2017): JARLE Volume VIII Issue 6(28) Fall 2017, 2017)
In the article considered demographic indicators of sustainable assessment of human resources in labor market of the integrated association of the countries of EEU. Also was studying of quantitative and qualitative tendencies of the integrated labor market revealing the forecast of a situation for prospect perspective. In EEU the observed the dispersion of human resources over the countries. There are objective reasons which are slowing down development of regional Eurasian integration. Disproportions in distribution of demographic potential over the countries of EEU will remain and in the future that will lead to strengthening of problems of misbalance of supply and demand of human resources in labor market of the general economic spatial association. Studying of features of the countries in formation of demographic indicators allows revealing priority problems and methods of regulation of the integrated labor market.